Symbole w społeczności regionu Zagłębia Dąbrowskiego - Walancik, Marek (Wydawnictwo Naukowe UAM, 2018)
The author attempts to characterize the region of Zagłębie Dąbrowskie, a region on the border between Silesia and Lesser Poland in geographical and cultural sense. He draws attention to the symbolism of the region and its acquaintance and significance in regional identity
Symbols in the Community of Zagłębie Dąbrowskie
Keywords: symbol; region; community; Zagłębie Dąbrowskie; regional identity